Site effect on seed germination of two species of Cladanthus in Morocco - Souad El Hafidi; Mohammed Ouhssine; Abderrahim Benzakour; Fatima Gaboun; Hamid Khamar; Khadija Bakhy; Abdelmonaim Homrani Bakali (African and Mediterranean Agricultural Journal - Al Awamia, 2022)
Seed germination of two species of the genus Cladanthus: Cladanthus mixtus (annual plant) and Cladanthus scariosus (perennial plant) was studied. The aim of this work was to determine germination differences at the inter-site level for both species (7 sites for each species) and at the intra-site level (Three accessions for each site) for C. mixtus. The germination test was carried out in a laboratory room at an average temperature of 18 °C. Six parameters were determined: Final germination percentage (FGP), mean germination time (MGT), coefficient of the variation of germination time (CVt), germination index (GI), coefficient of velocity of germination (CVG), and median germination time (T50). The average germination percentages were 95.2 and 83.8%, respectively for C. mixtus and C. scariosus. Germination time and speed were highly variable at the inter-site level for both species. The provenance of seeds significantly affects the germination capacity. Germination was better in the sites: Larache, Sidi Chafi and Sidi Taibi for C. mixtus and in Ijoukak 1 and Ijoukak 2 for C. scariosus. The mean values of C. mixtus and C. scariosus are respectively: 92.2-98.7% and 70.0-93.0%. The accession effect in C. mixtus was significant for the final germination percent at four sites (Larache, Boghadi, Harcha and Ain El Aouda). For other parameters (MGT, GI and CVG), significant differences were observed mainly in Tiddas and Boghadi. This inter-site variability must be considered for the ex-situ conservation and domestication initiation of C. mixtus and C. scariosus.